Internalisasi Nilai Toleransi dalam Pembelajaran Matematika di Tingkat Dasar - M Wahib; Isro'il, Ahmad; Maghfirotun, Khubni (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2024)
The value of tolerance is important to be instilled in students since an elementary level because tolerance is one of the basic values ​​contained in religious teachings. However, there has been no research that examines the internalization of tolerance values, especially in mathematics learning at the elementary level. This research aims to internalize the value of tolerance in mathematics learning at the elementary level. This research is a literature study research. The results of this research are alternatives that can be carried out in internalizing the value of tolerance in mathematics learning at the elementary level through positive negative symbols and block volumes. This can be analogous to an attitude of mutual respect and respect for differences in opinions, beliefs or views. By providing concrete examples of mathematical concepts that can be analogous to the value of tolerance, teachers can help students understand and internalize the value of tolerance. So that through learning mathematics teachers can instill the values ​​of tolerance in learning.